Quality of Life Among Cancer Survivors Challenges and Strategies for Oncology Professionals and Researchers (Springer International Publishing, 2018)
This multidisciplinary reference explores the concepts and realities of quality of life among cancer survivors in its physical, psychological, cognitive, social, and familial dimensions. Informed by a broad range of fields including genetics, psychiatry, nursing, dentistry, rehabilitation, and ethics, it addresses daily challenges of living for this population, from self-care to cultural concerns and from social interactions to experiences with providers. Family issues of pediatric, young adult, and elder survivors, caregiving parents, and siblings are a major area of concern. And contributors describe interventions for survivors as individuals, in family content, and as part of integrated care across primary and specialty settings. Included among the topics: Play, leisure activities, and cognitive health among older cancer survivors. Genetic mutations in cancer susceptibility genes: a family history of cancer. Cancer patients in a pediatric intensive care unit: a single center experience. The impact of childhood cancer on the quality of life among healthy siblings. When cancer returns: family caregivers and the hospice team. Experiencing cancer services: a story of survival and dissatisfaction. A significant addition to the cancer survivorship literature, Quality of Life Among Cancer Survivors is a practice-building resource for oncology and allied health professionals, health psychologists, and social workers, as well as researchers in these fields.